SISTEM PEMERINTAHAN WILAYAH MALANG PADA MASA KOLONIAL - Yuliati Yuliati (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2012)
Malang has a long history, From geopolitic point of view, Malang was under sovereignty of Hindu- Buddha, Islam. And the last, Malang was coloniaiizedby imperialists. In VOC colonialism period, Malang was under Pasuruhan residency. Finally, European settlements emerged. Malang as insulated region started to open after coffee cultivation. Agrarian Law and SugarAct in 1870 had made Malang grown rapidly. Agrarian Law had great impact on farm tenants who lived in rural area. It alsobrought out new farms. On the other hand, Sugar Act brought out large scale sugar industry which needed transportation by trains. Therefore, the relationship among Malang-Pasuruhan-surabaya could be enhanced.